Sustainable self-compacting concrete: effect of combined marble waste as fine and coarse aggregates - El Ghazali, Belgacem Mohamed; Ouldkhaoua, Younes; Herihiri , Ouided; Lyacia, Sadoudi; Arroudj, Karima (Vojnotehnički glasnik / Military Technical Courier, 2025)
Introduction/purpose: Environmental protection through waste recycling is one of the major challenges of our time. Inert waste, mainly generated by industry, makes up a significant portion that harms the environment due to its accumulation in nature. Methods: The primary objective of this study is to examine the influence of marble waste valorization as sand and gravel on the rheological and mechanical properties of self-compacting concrete (SCC). For this study, marble was used as fine aggregate sand (MAS) at rates of 10%, 20%, and 30%, and as coarse aggregate gravel (MAG) at a rate of 100%. Results and conclusions: The results of this study demonstrate that the introduction of marble waste (MW) as aggregate positively influenced the rheological characteristics, notably reducing the need for superplasticizer dosage. Additionally, in terms of mechanical outcomes, the use of MAG led to improved mechanical strengths.